THE THREE PHASES OF ISLAMIC STUDIES IN THE WEST: A CRITICAL EXAMINATION OF ORIENTALIST, MISSIONARY, AND COLONIAL LEGACIES - Afandi, Akhmad Jazuli (International Journal of Multidisciplinary Reseach, 2025)
This study critically analyzes the genealogical development of Islamic studies in the West through three interconnected historical phases—theological, political, and scientific—examining how Orientalism, missionary enterprise, and colonialism have shaped each stage. Employing genealogical and critical discourse analysis following Foucauldian frameworks, the investigation examines historical and academic texts to trace power-knowledge dynamics across these phases. Findings demonstrate that the theological phase (medieval period) featured Christian polemical traditions constructing Islam as a heretical deviation; the political phase (colonial era) transformed Orientalism into an administrative apparatus for governing Muslim populations; and the scientific phase (modern universities) maintained Orientalist residues despite objectivity claims. These three forces collectively generate knowledge regimes that systematically marginalize Islamic epistemology and silence Muslim scholarly voices. Theoretically, the findings underscore imperatives for Muslim-majority regions to critically examine their dependence on the Western academic paradigm, while advocating that Western institutions cultivate inclusive epistemic spaces that incorporate Muslim communities into knowledge production. The study recommends future research through case studies of national contexts, biographical examinations of influential scholars, and explorations of Islamic subfields via decolonial lenses. Also, establishing global Islamic studies networks based in Muslim contexts, democratizing academic access, and implementing dialogical, interdisciplinary approaches grounded in epistemic justice principles.